Academic Program Approval and Review Practices - Creamer, Don G.; Janosik, Steven M. (Education Policy Analysis Archives, 1999)
This report outlines general and specific processes for both program approval and program review practices found in 50 states and eight foreign countries and regions. Models that depict these procedures are defined and the strengths and weakness of each are discussed. Alternatives to current practice by state agencies in the U.S. are described that might provide for greater decentralization of these practices while maintaining institutional accountability.